Aternativa do controle sanitário de rebanhos leiteiros na prevenção de mamites bovinas de etiologia conhecida - Heloiza Maria de Souza (1988)
Six dairy farms were observed with emphasis placed. On the small dairy herd everage unit of productivity of the State of Minas Gerais, actually yielding not more than 4,5 to 5 liters/cow/day. Such a small dayly milk production is intimately related to a series of udder infectious diseases widely scattered among the dairy herds which were collectively diagnosed as mastitis. Three groups of dairy farms were examined bymeans of two different observation phases. The greater proportion of the diagnosed mastitis cases were considered under the sub-clinical status, consequently they were inapparent to clinical observations. The work included the confirmatory isolations of the various pathogenic etiological agentes from positive CMT (California Mastitis Test) sample and it was concluded that the Staphylococcus aureus accounted for the greatest one (65%). It was also observed that the introduction of simple hygienic sanitary procedures that still are not yet adopted by the farmers, is capable of minimizing the high incidence of infections and consequently would improve dayly milk productivity and the quality of the milk produced.